The Invisible Burden: A Review of Neuropsychiatric Symptoms in Parkinson's Disease and the Role of Interdisciplinary Palliative Care Strategies - Chioma Nwachukwu; Ijeoma Ogbonna; Ifeoma Achebe; Stephen Jesmajian; Jocelyn Jiao; Rita Caroline Crooms (American Journal of Hospice and Palliative Medicine®, 2026)
Parkinson’s disease (PD) is a neurodegenerative disease characterized by progressive loss of dopaminergic neurons, resulting in many motor and non-motor symptoms. The motor manifestations of PD are often the focus of medical interventions, yet non-motor symptoms may be equally burdensome for patients and caregivers. Neuropsychiatric symptoms such as anxiety, depression, psychosis, cognitive and impulse control disorders are frequently underdiagnosed in PD, yet they constitute a significant burden on the patients and caregivers. Palliative care (PC) addresses the physical, psychosocial, and existential suffering of patients with chronic illnesses to improve their quality of life, and recent evidence supports the role of PC in improving quality of life outcomes in PD patients and their caregivers. We propose that PC clinicians have an opportunity to facilitate early recognition of PD-associated neuropsychiatric disorders and that multidisciplinary care models integrating PC strategies present a promising avenue for improving behavioral outcomes in patients and decreasing caregiver stress. This narrative review provides an overview of the neuropsychiatric symptoms of PD, patient and caregiver burden, management gaps, and the potential role of interdisciplinary PC in bridging the existing gaps. Further research and education are needed to overcome barriers to PC accessibility and elucidate the optimal model for routine PC integration in comprehensively addressing the needs of PD patients.